PEMANFAATAN TEKNOLOGI VPN UNTUK MEMBANGUN SISTEM PEMBAYARAN BIAYA PENDIDIKAN SEKOLAH DI PD. BPR BKK DEMAK KOTA - Siswanto Siswanto (Universitas Sains dan Teknologi Komputer, 2018)
The development of science and technology in various fields in the era of globalization is felt to be very advanced. So that information is something that is needed in a fast, precise and accurate. Many conveniences are promised in a variety of information technologies. There is one fact that cannot be denied that this information has become an expensive commodity, if a company or agency cannot uphold the information that it needs most, then the procurement of information itself will obviously drain resources and funds. In doing business, PD. BPR BKK Demak Kota already has and uses an adequate accounting, deposit and credit information system. One of the strategies applied by PD. BPR BKK Demak Kota in collecting funds is the Ball Pick Up System, which is by visiting individual and institutional customers. While the institutions that have been served by PD. BPR BKK Demak Kota are schools, one of which is SMA Negeri 3 Demak. The service is in the form of an education fee payment. In serving the payment of school education costs in SMA 3 Demak, PD. BPR BKK Demak Kota still uses the conventional way, that is by receiving deposits from students, the data is recorded in the admission book and after adding up with a calculator, the result is that service is very slow. To overcome the problems mentioned above, it is necessary to build a system that can accelerate the process of receiving tuition fee payments and can produce a more detailed report on school fees both those who have paid and those who have not yet paid. One such system is utilizing VPN (Virtual Private Notwork) technology. Based on the description of the problem above, it becomes an impetus for the writer to be able to solve this system as well as possible and is very background for the writing of the Thesis which is planned to be realized using the Microsoft Visual Basic 6.0 program language